Variable threshold energy detection algorithm based on trust degree - Jie XIAO; Yuebin CHEN; Chutian CHEN; Ting ZHENG; Jiwu QIAN (Dianxin kexue)
Aiming at stochastic probabilistic SSDF attacks,a variable threshold energy detection algorithm based on trust degree was proposed.Firstly,the variable threshold was updated by comparing the actual fusion value with the upper and lower boundary values of the fusion center.The upper and lower boundary values were determined through the given false alarm probability andmissed probability.Secondly,a soft fusionmethod was used based on the ratio of correct perception times and the total number of times to update the trust value.Simulation results show that,compared with the traditional fixed threshold,the proposed algorithm can not only reduce the false alarm andmissed detection probability,but also improve the detection probability of the system.